Fundamentals of engineering thermodynamics - Moran, Michael J.; Shapiro, Howard N. (John Wiley & Sons, 2004)
A comprehensive, best-selling introduction to the basics of engineering thermodynamics. Requiring only college-level physics and calculus, this popular book includes a realistic art program to give more realism to engineering devices and systems. A tested and proven problem-solving methodology encourages readers to think systematically and develop an orderly approach to problem solving: Provides readers with a state-of-the art introduction to second law analysis ; Design/open-ended problems provide readers with brief design experiences that offer them opportunities to apply constraints and consider alternatives.